Improving Reading Achievements in Descriptive Text by Using TPRC (Think, Predict, Read and Connect) Strategy - Sholikhah, Hani Atus; Azizah, Mar’atul (Faculty of Education and Teacher Training of UINSI Samarinda, 2019)
This research investigates about the use of TPRC strategy to improve reading achievement in descriptive text of the eleventh graders of MTS Nurul Falah Kutapandan . The research is conducted based on the main problems: (1) Is there any significant difference in reading achievement using descriptive text between students who are taught by using TPRC strategy and those who are not? (2) Does TPRC strategy give contribution to the students’ better achievement in reading and listening skills or not? To answer the questions, the researcher collect data from 64 students as a sample in two classes, one class as experimental research method. The researcher chosen two classes as a sample while class eight graders is experiment method, the data is gathered through pre-test and post-test. The result data were analyzed by calculated by using SPSS 21 version. Based on the result paired sample t-test in reading there were found: first, the mean score of pretest in the experimental group was 58.37 and posttest was 79.78. Second, mean score of pretest in control group was 57.15 and posttest was 71.46.